The effect of smoking on the symptoms and progression of multiple sclerosis: a review - Afsaneh Shirani; Helen Tremlett (Dove Medical Press, 2010)
Afsaneh Shirani1, Helen Tremlett1,21Faculty of Medicine, Division of Neurology, University of British Columbia, Vancouver, Canada; 2Brain Research Centre, University of British Columbia, Vancouver, CanadaAbstract: Multiple sclerosis (MS) is a chronic inflammatory neurodegenerative disorder of the central nervous system with characteristic demyelinating lesions and axonal loss. MS accounts for the most common cause of neurological disability in young adults in the Western world. The clinical manifestations and the course of MS are highly variable. The early stage of the disease is usually characterized by attacks of neurological dysfunction with complete or incomplete recovery, however, with time disability accumulates in many patients. MS is believed to result from an interplay between susceptibility genes and environmental factors, one of which is smoking. Smoking, a worldwide epidemic, can be regarded as an important risk factor for MS particularly because of its modifiable nature in the quest to prevent or temper the disease course in MS as well as providing possible insights into MS pathogenesis. There are also reports that smoking may influence the symptoms and disease progression in patients with MS. The purpose of this article is to review the effects of smoking on MS symptoms and progression. We conclude that (1) although there are some early reports on worsening of MS symptoms by smoking, the existing evidence is insufficient to thoroughly assess the effects of smoking on the myriad of MS symptoms and (2) smoking seems to adversely influence disease progression in MS patients. We also discuss the potential biological mechanisms linking smoking and MS.Keywords: smoking, multiple sclerosis, disease progression, symptoms